2013
DOI: 10.1115/1.4024867
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of a Parametric Variation of the Rim Seal Geometry on the Interaction Between Hub Leakage and Mainstream Flows in High Pressure Turbines

Abstract: The objective ofthis work was to assess and understand the effects of a parametric variation performed on a typical overlapping rim seal geometry. The datum geometry has been the focus of a detailed experimental investigation employing a large-scale linear cascade subjected to a range of the mass flow rates and swirl velocities of the leakage air. The parametric variations described in this paper were examined using validated computational fluid dynamics (CFD). As a part of the parametric studies, both the axi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The correlation from Churchill and Ozoe [26], Eqn. (10), was used to estimate the laminar NuD with n set to 10. Graetz number (Gz) was computed using the hydraulic diameter of each station in Fig.…”
Section: Nusselt Number Comparison With Pipe Flowmentioning
confidence: 99%
See 1 more Smart Citation
“…The correlation from Churchill and Ozoe [26], Eqn. (10), was used to estimate the laminar NuD with n set to 10. Graetz number (Gz) was computed using the hydraulic diameter of each station in Fig.…”
Section: Nusselt Number Comparison With Pipe Flowmentioning
confidence: 99%
“…Popović and Hodson [9] investigated the effect of changing the overlap of the rim seal geometry on sealing effectiveness and the effect on the passage vortex using a linear experimental rig. In 2013, Popović and Hodson [10] experimentally tested a variety of seal designs that are similar to what is currently used in industry. They discovered that an inclined ejection does not result in a strong leakage vortex.…”
Section: Introductionmentioning
confidence: 99%
“…Thrift et al [5] Contributed by the International Gas Turbine Institute (IGTI) of ASME for publication in the JOURNAL OF showed a dramatic difference in the development of the horseshoe vortex upstream of a vane as a function of slot orientation angle, with a 45 deg slot essentially eliminating the development of the vortex and providing almost 150% improvement in the coolant coverage. A series of studies [6][7][8] investigated the leakage from realistic rim seals with representative tangential velocity. Their work showed the importance of a recirculating vortex in the upstream cavity on aerodynamic loss generation, with the best performance when the vortex was moved further into the rim seal, and the blade-vane overlap was made as smooth as possible.…”
Section: Relevant Past Studiesmentioning
confidence: 99%
“…In 1988, Phadke and Owen [13] studied seven sealing structures with different complexity levels, including a radial sealing structure and an axial sealing structure, and obtained the correlations of the minimum sealing flow. In 2012, Popovic and Howard et al [14] studied the characteristics of the same sealing structure by altering the parameters of its geometry. Subsequently, Mi-Ae Moon [15] added a fin based on this Ivan geometry, and the results showed that the fin could significantly block the ingress fluid.…”
Section: Introductionmentioning
confidence: 99%